Pemilihan Lokasi Bandar Udara Kabupaten Kolaka Utara Berbasis Analytical Hierarchy Process (AHP) - Muhammad Fatwa Japari, Dewa; Yamin Jinca, Muh.; Fathien Azmy, Muhammad (Politeknik Penerbangan Makassar, 2020)
The availability of transportation infrastructure and facilities is a major requirementin supporting the development of ​​a region, especially for regions that have large potential resources, but are not supportedby adequate infrastructure and transportations. In the regional spatial plan (RTRW) North Kolaka Regency explained that there are three alternative airport construction sites. Using the projection method andqualitative description to find out population projections, projectionsof estimated number of air transport passengers, and regional transportation systems fromand towards North Kolaka and its surroundings, using the Analytical Hierarchy Process (AHP) method to determine alternative locations for the deveolopment of new airport. Based on the results of the analysis, the most strategic location forairport development which is Kodeoha District with a weight value of 0.47. Weight values ​​indicate that the best alternative location of the three alternativesthe location is supported by nine aspects mainly from economic, topographic, and surface conditions. This is due to being in the middle North Kolaka Regency and has land with the potential to develop an airport that is an area of ​​ponds and rice fields that are no longer productive.